Can Autocracy Promote Literacy? Evidence from a Cultural Alignment Success Story - Nuno Palma; Jaime Reis (European Historical Economics Society (EHES), 2018)
Do countries with less democratic forms of government necessarily have lower literacy rates as a consequence? Using a random sample of 4,600+ individuals from military archives in Portugal, we show that 20-year old males were twice as likely to end up literate under an authoritarian regime than under a democratic one. Our results are robust to controlling for a host of factors including economic growth, the disease environment, and regional fixed-effects. We argue for a political economy and cultural explanation for the success of the authoritarian regime in promoting basic education.
Keywords: H41; I24; I25; N33; N34; O12; 330; Anthropometrics; economic history of education; public schooling provison; political economy of development